Training on Rice Straw Ammoniation Technology as an Alternative Feed for Ruminant Livestock During the Dry Season in Wangka Village - Laurensius Meze Mala; Yohanes Freadyanus Kasi; German Yohanes Sola (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
The abundant supply of rice straw in Wangka Village has not been optimally utilized as livestock feed, while livestock farmers face a shortage of forage, especially during the dry season. This community service activity aims to improve the knowledge and skills of farmer-livestock breeders in utilizing rice straw as an alternative feed through ammoniation technology using urea fertilizer. The activity was conducted on May 8, 2026, involving 15 participants consisting of farmers and livestock breeders. The methods used included training sessions, demonstrations, hands-on practice, mentoring, and monitoring throughout the 21–28-day fermentation process. Evaluation was conducted through a post-test, observation of practical skills, and monitoring of the rice straw fermentation results. The evaluation results showed that 12 out of 15 participants (80%) understood the procedure for producing ammoniated straw and were able to practice it independently, while 3 participants (20%) still required guidance, particularly regarding urea dosage determination and storage techniques during fermentation. Monitoring results showed that the resulting ammonia-treated straw had a softer texture, a yellowish-brown color, a characteristic ammonia odor, and did not rot, making it suitable for use as livestock feed. In addition, 10 out of 15 participants (66.7%) stated that they would continue to apply the ammonia treatment technology in the next harvest season. These findings indicate that training on rice straw ammoniation technology is effective in building community capacity, promoting the adoption of appropriate technologies, and supporting the sustainable supply of livestock feed during the dry season.